Characteristics and Outcomes of Cases of Children and Adolescents With Pediatric Inflammatory Multisystem Syndrome in a Tertiary Care Center in Mexico City - Gil Guevara, Ricardo; Marroquín Yáñez, María de Lourdes; Jiménez-Juárez, Rodolfo Norberto; Olivar Lopez, Víctor; Chávez Lopez, Adrián; Sienra Monge, Juan José Luis; Jamaica Balderas, Lourdes Maria del Carmen; Martínez Herrera, Silvia Alexandra; Domínguez-Barrera, Clemen; Erdmenger Orellana, Julio; Márquez González, Horacio; Klünder-Klünder, Miguel; et al. (Frontiers in Pediatrics, 2022)
Background: pediatric inflammatory multisystem syndrome (PIMS) is a complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children that resembles Kawasaki syndrome and places them at high risk of cardiorespiratory instability and/or cardiac damage. This study describes the clinical presentation and outcomes of patients with PIMS in Mexico City. Methods: observational study of children hospitalized for PIMS based on the CDC case definition criteria, in a single tertiary care pediatric center in Mexico City between May 1, 2020, and September 30, 2021. Demographic characteristics, epidemiological data, medical history, laboratory tests, cardiology evaluations, treatment, and clinical outcomes were analyzed. Results: 75 cases fulfilled the case definition criteria for PIMS (median age: 10.9 years, Interquartile range [IQR]: 5.6–15.6). Fifteen (20%) patients had severe underlying disease, 48 (64%) were admitted to the intensive care unit, 33 (44%) required invasive mechanical ventilation and 39 (52%) received vasopressor support. The patients were clustered through latent class analysis based on identified symptoms: Cluster 1 had rash or gastrointestinal symptoms (n = 60) and cluster 2 were those with predominantly respiratory manifestations (n = 15). Two patients (2.7%) died, and both had severe underlying conditions. Five patients (6.7%), all from cluster 1, developed coronary aneurysms. Conclusion: There were a high proportion of patients with severe respiratory involvement and positive RT-PCR SARS-CoV-2 and few cases of coronary aneurysms in our study which suggests that a high proportion of the children had severe acute COVID-19. The clinical manifestations and outcomes are comparable to previously reported international studies.